Cochlear implantation under local anesthetic: A systematic review and meta‐analysis. Issue 1 (5th January 2022) - Walters, Ben; Gaskell, Peter; Muzaffar, Jameel; Iftikhar, Haissan; Monksfield, Peter; Bance, Manohar
Abstract: Objectives: As the population ages and implantation criteria are relaxed, more patients with complex comorbidities are becoming eligible for cochlear implantation (CI). These patients have higher risks associated with general anesthesia. This systematic review assesses outcomes and complications following CI under local anesthetic to examine utility for patients deemed not suitable or at high risk for general anesthesia. Methods: A systematic review and meta‐analysis performed according to the 2020 PRISMA guidelines. Databases searched were MEDLINE, PubMed, EMBASE, CINAHL, Web of Science Core Collection, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials and ClinicalTrials.gov . There were no limitations on year of publication or language. Results: Then, 132 unique were identified. After screening abstracts and full texts for eligibility criteria a total of 18 articles were included. In the nine studies where audiological data were reported, all patients demonstrated improvement in audiological outcomes following implantation under local anesthetic (LA). Only minor complications of transient vertigo, wound infection, facial nerve paralysis, confusion, and tinnitus were reported but all were transient. Meta‐analysis showed surgical time was significantly shorter under LA. Conclusions: CI under LA is safe for patients with comorbidities which preclude them from general anesthesia, with minimal complications and an improved cost‐effectiveness profile. However, larger scale, robust trials are required to assess this further. Abstract : Cochlear implantation under local anesthetic is safe for patients with comorbidities which preclude them from general anesthesia, with minimal complications and an improved cost‐effectiveness profile. However, larger scale, robust trials are required to assess this further.